Dielectric properties of soft chemical method derived CaCu3Ti4O12 thin films onto Pt/TiO2/Si(100) substrates - Moura, F.; Aguiar, E. C. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Simões, Alexandre Zirpoli [UNESP] (Elsevier B.V. Sa, 2011)
Calcium copper titanate, CaCu3Ti4O12 (CCTO), thin film has been deposited by the soft chemical method on Pt/Ti/SiO2/Si (1 0 0) substrates at 700 degrees C for 2 h. The peaks were indexed as cubic phase belonging to the Im-3 space group. The film exhibited a duplex microstructure consisting of large grains of 130 nm in length and regions of fine grains (less than 80 nm). The CCTO film capacitor showed a dielectric loss of 0.031 and a dielectric permittivity of 1020 at 1 MHz. The J-V behavior is completely symmetrical, regardless of whether the conduction is limited by interfacial barriers or by bulk-like mechanisms. Based on impedance analyses, the equivalent circuit of CCTO film consisting of a resistor connected in series with two resistor-capacitor (RC) elements. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Thin films; Dielectrics; Chemical synthesis; X-ray diffraction